On some spectral properties of TanDEM-X interferograms over forested areas - De Zan, Francesco; Krieger, Gerhard; Lopez-Dekker, Paco (IEEE Geoscience and Remote Sensing Letters, 2013)
This letter reports about some obervations over rainforest (in Brazil and Indonesia), where the spectra of TanDEM-X interferograms show distinct features, almost a signature, which is explained and modelled in terms of the scattering properties. Supported by comparisons with simulations, the observations exclude any homogeneous, horizontally-layered forest; instead, they are compatible with a model with point scatterers clustered in clouds. Such a model, with high extinction and large gaps that allow significant penetration, is able to explain to a good degree the observations.
DLR Import::2019-04-02
Keywords: Synthetic aperture radar (SAR) interferometry